Seasonal Changes in Soil Respiration Of Degraded And Non-Degraded Sites in Oak and Pine Forests of Central Himalaya - Jina, BS; Bohra, CPS; Rawat, YS; Bhatt, MD (Scientific World, 2010)
Present investigation deals with the seasonal changes in soil respiration of degraded and non-degraded oak and pine forests in Van Panchayat of Kumaun Himalaya. Soil temperature and soil moisture enhances soil respiration by increasing microbial activity and decomposition of organic matter. The rate of soil respiration was higher in non-degraded site of oak forest in Dhaili VP (63.9±1.6 to 363.6±5.3 mg CO2 m-2h-1), non-degraded site of pine forest (39.1±0.9 to 195.41.6 mg CO2 m-2h-1) in Guna VP, and lower in degraded pine forest in Toli VP (21.3±0.5 to 126.8±0.8 mg CO2 m-2h-1), degraded oak forest of Guna VP was (26.9±0.8 to 167.3±1.2 mg CO2 m-2h-1). Within non-degraded and degraded sites of both oak and pine forests soil respiration was positively correlated with soil temperature and soil moisture. Key words: Soil respiration; Degraded; Non-dedgraded; Van panchayat. DOI: 10.3126/sw.v6i6.2641 Scientific World, Vol. 6, No. 6, July 2008 89-93